Akselerasi Sertifikasi Halal melalui Pendampingan Implementasi Sistem Jaminan Produk Halal pada Rumah Potong Unggas Ba’i Mulya Kesesi - Adinugraha, Hendri Hermawan; Dewi, Anggun Rahadian Kusuma; Nasarruddin, Razie Bin (Dharmahita: Journal of Community Service and Development, 2026)
Increased public awareness of halal product consumption requires food businesses, including poultry slaughterhouses (RPU), to fulfill their halal certification obligations as stipulated in Law No. 33 of 2014 concerning Halal Product Guarantee. However, small and medium-sized RPU still face limitations in halal literacy, understanding of regulations, and the ability to comprehensively implement the Halal Product Guarantee System (SJPH). This community service activity aims to accelerate the halal certification process through assistance in implementing SJPH at the Ba’i Mulya Kesesi Poultry Slaughterhouse in Pekalongan Regency. The method used was participatory assistance with stages of field observation, structured interviews, halal education, technical guidance on the preparation of SJPH documents, standardization of operational procedures for poultry slaughter in accordance with Islamic law, and assistance with halal certification registration. The results of the activity showed a significant increase in the managerial and administrative capacity of the partners, as evidenced by the formulation of written halal policies, the formation of an internal Halal Management Team, the development of standard operating procedures for halal slaughter, and the implementation of a daily hygiene and production recording system. The partners demonstrated an increased understanding and commitment to the sustainable application of halal and thayyib principles. This activity successfully improved the readiness of the Ba’i Mulya Poultry Slaughterhouse in applying for official halal certification. Assistance with the implementation of SJPH proved effective in accelerating halal certification while strengthening business management grounded in Islamic economic values.